The Improvement of Community Capacity in Facing of the Landslide in Sukajaya Subdistrict of Bogor Regency - Sumantri, Siswo Hadi; Kurniadi, Anwar; Marnani, Christine; Sutawidjaya, Ahmad Hidayat (Technium Social Sciences Journal, 2021)
The improvement of community capacity in facing the landslide is one of the best ways to avoid community from bad impact of this disaster. Even though, in the field, program of the improvement of community capacity must be accordance with the kind and level of impact. The purpose of this research was analyzing the improvement of community capacity in facing of the landslide. Research method used qualitative and phenomenology design, and data analyze used Miles & Hubermen & Saldana. The results of this research were a) assessment of risk disaster showed Sukajaya Subdistrict has middle to high level of landslide-prone; b) the knowledge, innovation and cultures showed enough to help the disaster management on the next time; c) the application of disaster risk reduction involved spatial management, land use for community agriculture, making new national park, and making disaster resilience village; d) the application disaster mitigation pre disaster with building permanent shelters, and post disaster by rehabilitation and reconstruction, reforestation and conservation; e) the strengthen of preparedness could take advantage of knowledge and awareness of community that have been high level. Suggestions were involved disaster program in local rules of Bogor Regency, continuing conservation program, conducting preparedness training program, and continuing mitigation program post disaster.